Full Costing Analysis of Power Generation Supply Costs: Differences Across Power Plant Types in 2023 - Heryawan, Heryawan; Prasetyo, Tri Joko; Syaipudin, Usep (Jurnal Economic Resource, 2024)
Electricity production costs in power plants are closely linked to electricity tariffs (selling prices). To fund power generation, both direct and indirect costs, including basic and overhead costs, are calculated as components of the Power Generation Supply Cost (BPP). Changes in BPP components impact overall costs, affecting total BPP. This study aims to compare and analyze cost differences among PLN power plants and identify which types of power plants show significant cost variations. Conducted at PT PLN (Persero) in 2023, the research uses an exploratory descriptive method with quantitative data from financial reports and time-series data. The study examines four BPP subcategories across 38 power plants, grouped into six categories. Multivariate analysis is applied using SPSS. Results show that power plant groups significantly influence inefficiencies in BPP. Specifically, BPP A has inconsistent cost variations, with high deviations in fixed asset depreciation, leased asset depreciation, and loan expenses. Certain power plants show inefficiencies affecting BPP. PLTGU and PLTD contribute the highest costs in BPP A and BPP D, respectively. Overall, PLTU is the most efficient group, significantly impacting BPP elasticity.